The role of stereotypical information on medical judgements for black and white patients. - Filipa Madeira; Rui Costa-Lopes; Emerson Araújo Do Bú; Rui Tato Marinho (PLoS ONE)
THIS ARTICLE USES WORDS OR LANGUAGE THAT IS CONSIDERED PROFANE, VULGAR, OR OFFENSIVE BY SOME READERS. The new generation of direct-acting antivirals has improved dramatically the rates of cure for chronic hepatitis C. Yet, evidence shows that racial groups are deemed more often ineligible for hepatitis C treatment, despite no clinical evidence supporting differential treatment for Black and White patients. One possible explanation has to do with providers' racial biases. This investigation sought to explore medical students' racial stereotypes (Study 1, N = 171) and the role of stereotypical cues on perceptions of medical adherence of Black and White patients (Study 2, N = 208). In Study 1, we first sought to identify health-related aspects that are consistently associated with Blacks as part of a stereotype. In Study 2, we experimentally manipulated racial stereotypes identified in Study 1 by asking participants to read a clinical vignette depicting a patient (Black vs. White) and their medical history (cause of exposure to hepatitis C: unprotected sex vs. non-injectable drugs use). The results show that the impact of stereotypicality on patient perceived compliance varies as a function of medical students' racial prejudice. Implications for further applied health inequalities research and for medical training are discussed.